Estudos da técnica de beamforming combinando arranjos de microfones e material poroso - Pozzer, Talita (2017)
In order to solve the problems caused by noise, it is essential that an adequate evaluation of the main sources of noise is carried out. This can be done using an acoustic imaging technique and one of them is the beamforming. Beamforming is a technique that consists of measuring the sound pressure of the source of interest by using a microphone array. After that the measured data goes to a post-processing generating an acoustic image of the source. Through that the main regions of sound radiation is shown. In this context usually outdoor measurements are taken. In this situation the microphones must be protected from the wind. For this purpose a layer of porous material may be used in front of the microphone array. Then its influence on the beamforming response is unknown. This work aims to evaluate the effect of the use of porous material on the microphone arrays at the beamforming response, using a free field directions vector hypothesis. For do this the porous material was first characterized according to its macroscopic parameters through impedance tube measurement. Then simulations were performed where it was possible to compare different materials and to test the influence of each macroscopic parameter on the array response. Measurements were also made in a semi-anechoic room where it was possible to evaluate the effect of distance between source and array, the deviation due to use different signals for evaluation, the three-dimensional beamforming preview and the recognitiopn of two sources by the array response. This methodology allowed to verify that the porous material cause a negatively affects on the array response through increasing the beamwidth. In other words, it increases the difficulty of the array to locate sources for certain frequencies. On the other hand the dynamic range increased with the use of the porous material representing a seeming improvement in the array response. However this increase is usually less than 2 [dB] what is not very representative. Moreover the sample thickness of the porous material was identified as the main characteristic that affects the array response. The thinner thicknesses have less influence on the array response thus having better results.